Analisis Kesulitan Belajar Matematika Pada Materi Operasi Hitung Perkalian Dan Pembagian Siswa Kelas IV SDN 02 Kedungwuluh Kabupaten Banyumas - Ubaidilah Digma Anggara; Pamujo (UM Purwokerto Press, 2026)
This study aims to analyse the learning difficulties experienced by fourth-grade students at SDN 2 Kedungwuluh in understanding multiplication and division operations, identify the factors causing these difficulties, and describe the efforts made by teachers to overcome them. The method used is a descriptive qualitative approach with a case study type. Data collection techniques were conducted through observation, interviews, and documentation. The results of the study indicate that students experience difficulties in understanding the basic concepts of multiplication and division, performing calculations, and solving word problems. Factors contributing to these learning difficulties include low numeracy skills, lack of understanding of mathematical symbols, and limited variety in the teaching methods and media used by teachers. To overcome this, teachers made various efforts such as providing individual guidance, using concrete media, and adjusting learning strategies according to student characteristics. This study is expected to serve as a reference in improving the quality of mathematics learning at the primary school level.